CLASSROOM INTERACTION AS AN ESSENTIAL FOR LEARNING THE ENGLISH IN PRIMARY SCHOOL CONTEXT - Nurmetova, Mokhimjon (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the classroom interaction, its importance and role in primary school education. In addition, listening, speaking, reading and writing skills are mentioned with the developmental ways and the role of communicative approach in teaching English language for young learners.